Efektivitas Bimbingan Klasikal dengan Media Film Pendek untuk Meningkatkan Empati Siswa di SMP Negeri 21 Samarinda - Firyal Adilah Syadza; Yasintha Sari Pratiwi; Dwi Sona; Muhaimin Abdillah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the effectiveness of classical guidance services using short film media in increasing students' empathy at SMP Negeri 21 Samarinda. This study uses a quantitative approach with a quasi-experimental design through a non-randomized control group pretest-posttest design. The research sample was determined using a purposive sampling technique involving eighth-grade students of SMP Negeri 21 Samarinda who were divided into an experimental group and a control group. Data were collected using a Likert-style empathy scale that measures aspects of perspective taking, empathic concern, personal distress, and fantasy. Data analysis was carried out using SPSS 27 through normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. The results showed that there was an increase in the level of empathy in the experimental group after receiving classical guidance services with short film media. The calculation of the N-Gain score in the experimental group was 60.5% which was included in the fairly effective category. The results of statistical tests showed a significant difference between the pretest and posttest scores in the experimental group, as well as differences in results between the experimental group and the control group. Thus, classical guidance services using short films are effective in increasing student empathy at SMP Negeri 21 Samarinda.